High-water-resistance soybean protein adhesive as well as preparation method and application thereof
By using green crosslinking agents and metal catalysts prepared by glucose and citric acid in soy protein adhesives, a crosslinking network structure is formed, which solves the shortcomings of existing adhesives in water resistance and hot pressing temperature, and achieves high Water resistance and effect that meets the requirements of Class II plates.
Patent Information
- Application Number
- CN202411293703.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-02-07
AI Technical Summary
The existing soy protein adhesives have shortcomings in water resistance and hot pressing temperature, especially in terms of boiling water wet strength and hot pressing temperature requirements.
Green crosslinking agent (GA) was prepared by pre-heat treatment of glucose and citric acid, and added to soy protein solution. The esterification and amidation reaction of hot pressing will be carried out to form a crosslinking network structure. A metal catalyst is added during the process to improve adhesiveness. performance of agent.
It significantly improves the water resistance and bonding strength of soy protein adhesives, meets the requirements of Class II boards, and reduces the hot pressing temperature, which is suitable for the production of artificial boards.
Smart Images

Figure BDA0005045318520000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wood adhesives, and in particular relates to a highly water-resistant soybean protein adhesive and a preparation method and application thereof. Background Art
[0002] Citric acid and glucose from all-biomass raw materials are polymerized as wood adhesives. During the hot pressing process, the three -COOH groups in the citric acid molecule and the multiple -OH groups in the glucose molecule are dehydrated and polymerized to form a wood adhesive, showing good bonding strength and water resistance. However, in the literature, the hot pressing temperature of the board with this formula is as high as 190°C, which has certain cost limitations in practical applications. However, this research report shows that citric acid can be used as a coupling agent to form a macromolecular substance through an esterification reaction with a substance containing a hydroxyl group through dehydration condensation, and is suitable for wood bonding.
[0003] The high viscosity, short service life, poor water resistance, and inconsistent composition and performance of protein-based adhesives have brought challenges to their use and promotion. Therefore, proteins must be modified to enhance their water resistance, processability, and bonding strength, thereby improving their overall performance. Alternatively, coupling agents can be used to increase the cross-linking density between them, thereby improving their water resistance. For example, by adding cross-linking agents (epoxides, aldehyde derivatives, isocyanates, hexachlorocyclotriphosphazenes, polyacrylates), the intermolecular forces can be converted from hydrogen bonds to covalent bonds, thereby forming a dense water-resistant structure, which successfully improves the bonding strength of the adhesive.
[0004] However, the crosslinking agents commonly used to modify soybean protein are derived from non-renewable petrochemical raw materials, and considering renewable recycling, biomass crosslinking agents have become the first choice. Literature reports that a research team used citric acid (CA) as a crosslinking agent to modify soybean protein and successfully prepared a warm water-resistant protein-based adhesive. The hot pressing temperature of this type of adhesive has dropped to about 180°C, and the performance of the board meets the requirements of the national standard Class II board, but the boiling water resistance wet strength is not ideal. The possible reason is that citric acid is rich in multiple carboxyl groups that are not completely consumed by the hydroxyl groups in soybean protein, resulting in its cured structure containing hydrophilic groups, which makes it easy for moisture to invade the glue layer interface. In addition, the free carboxyl structure is easy to ionize hydrogen ions in the water environment, presenting an acidic environment, aggravating the hydrolysis of the ester bond structure, and further disintegrating the cured glue layer structure, resulting in a significant decrease in its water resistance. On this basis, metal catalysts such as sodium-copper (II) salt (Collins reagent) are also used. The addition of the catalyst catalyzes the oxidation of the hydroxyl groups of glucose into aldehydes, ketones or carboxyl groups during hot pressing, which is more conducive to the formation of a body structure. This not only improves the mechanical properties, but also further reduces the platen temperature to 140°C and can meet the requirements of Class II plates (shear strength greater than 0.7MPa in 63°C hot water for 3 hours).
[0005] Therefore, how to solve the above problems and provide a sheet adhesive with better water resistance is a technical problem that needs to be solved urgently in industrial production. Summary of the invention
[0006] The purpose of the present invention is to provide a highly water-resistant soy protein adhesive with a relatively low curing temperature and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art. A green crosslinking agent (GA) is prepared by pre-heat treatment of glucose and citric acid, and then added to a soy protein solution, and hot-pressed to cause esterification and amidation reactions to form a crosslinked network structure.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] The first object of the present invention is to provide a highly water-resistant soy protein adhesive, wherein the soy protein adhesive is resistant to boiling water for at least 3 hours, and the preparation method of the soy protein adhesive comprises the following steps:
[0009] S1, preparing a cross-linking agent by pre-heat treatment of glucose and citric acid;
[0010] S2, adding the cross-linking agent into the soybean protein solution, and mixing to obtain a process solution;
[0011] S3, hot-pressing the process solution to make it undergo esterification and amidation reactions to obtain the highly water-resistant soybean protein adhesive.
[0012] Furthermore, the method further comprises adding a metal catalyst into the process solution, wherein the metal catalyst comprises any one of copper chloride, copper oxide or Collins reagent.
[0013] Furthermore, the mass ratio of the soy protein, glucose and citric acid is 1:(1-4):(0.6-2.4).
[0014] Furthermore, the temperature of the heat treatment is 70-80°C.
[0015] Furthermore, the mass ratio of the cross-linking agent to the soybean protein solution is 1:(0.5-2).
[0016] The second object of the present invention is to provide an aldehyde-free adhesive comprising the above-mentioned soy protein adhesive.
[0017] The main ingredient of the formaldehyde-free adhesive product is the soybean protein adhesive, and may also include auxiliary agents such as a curing agent, a toughening agent, a diluent, a filler or a modifier.
[0018] The curing agent is a component that accelerates the curing of the bonding material through chemical reactions. It is the most important compounding material in the adhesive. The curing agent reacts with the main polymer directly or through a catalyst to transform the originally soluble and fusible linear structure polymer compound into an insoluble and infusible bulk structure.
[0019] Toughening agent is a component to improve the toughness of the bonding layer and enhance its impact strength. Commonly used toughening agents include dibutyl phthalate and dioctyl phthalate.
[0020] Diluents, also known as solvents, mainly reduce the viscosity of adhesives to improve the wettability and fluidity of adhesives. Commonly used diluents include acetone, benzene and toluene. Fillers generally do not react chemically in adhesives, but can improve the strength, impact toughness and wear resistance of adhesive joints. Commonly used fillers include aluminum powder.
[0021] In order to meet specific physical and chemical properties, modifiers and other additives may also be added, such as coupling agents, initiators, promoters, thickeners, antioxidants, inhibitors, stabilizers, etc.
[0022] The third object of the present invention is to provide the use of the above-mentioned soybean protein adhesive or the above-mentioned formaldehyde-free adhesive in the preparation of artificial board products.
[0023] Furthermore, the artificial board product includes any one of plywood, particle board, fiberboard, blockboard and decorative board.
[0024] The fourth object of the present invention is to provide a method for preparing plywood, wherein the plywood is glued with the above-mentioned soy protein adhesive at a thickness of 200 g / m 2 The glue coating amount is applied to both sides of the board, the hot pressing temperature is 170-190℃, the pressure is 1.2MPa, the hot pressing time is 5min, and it is made by dry heat method.
[0025] The fifth object of the present invention is to provide a plywood produced by the above-mentioned preparation method.
[0026] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0027] (1) The present invention utilizes the structural characteristics of soybean protein containing a large number of -COOH, -NH2 and -OH groups, and utilizes these active functional groups to react with citric acid molecules containing three -COOH groups and one -OH group, and glucose molecules containing five -OH groups and one -CHO group, to form a thermosetting cross-linked network through esterification and amidation polymerization during a hot pressing process at 170°C, thereby forming an effective glue layer between the woods and achieving a good bonding effect, greatly improving water resistance, and the 3h boiling water immersion strength exceeding 0.7MPa.
[0028] (2) The present invention prepares a green crosslinking agent (GA) by pre-heat treatment of glucose and citric acid, adds the green crosslinking agent (GA) to a soy protein solution, and heat-presses the solution to cause esterification and amidation to form a crosslinked network structure.
[0029] (3) When a metal catalyst such as cupric chloride is added, the prepared adhesive meets the requirements of Class II boards (the shear strength is greater than 0.7 MPa after 3 hours in hot water at 63°C) and the hot pressing temperature is lower.
[0030] (4) The soybean protein adhesive provided by the present invention is suitable for bonding wood fiber powder, particles, plates, etc. It is suitable for the preparation and production of artificial boards (plywood, fiberboard, particleboard), and the artificial board products produced can meet the environmental protection requirements of ENF level. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0032] Example 1
[0033] This embodiment provides a method for preparing a highly water-resistant soybean protein adhesive. The mass ratio of soybean protein powder: glucose: citric acid is 1:1:0.6. The specific steps are as follows:
[0034] 5 parts of glucose, 2 parts of pure water, and 3 parts of citric acid were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred at a mass ratio of 2:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:1:0.6) to obtain a soy protein adhesive.
[0035] Example 2
[0036] This embodiment provides a method for preparing a highly water-resistant soybean protein adhesive. The mass ratio of soybean protein powder: glucose: citric acid is 1:2:1.2. The specific steps are as follows:
[0037] 5 parts of glucose, 2 parts of pure water, and 3 parts of citric acid were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was dissolved in pure water with a soy protein mass fraction of 25%, and stirred for 5 minutes until it was uniform. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred in a mass ratio of 1:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:2:1.2) to obtain a soy protein adhesive.
[0038] Example 3
[0039] This embodiment provides a method for preparing a highly water-resistant soybean protein adhesive. The mass ratio of soybean protein powder: glucose: citric acid is 1:4:2.4. The specific steps are as follows:
[0040] 5 parts of glucose, 2 parts of pure water, and 3 parts of citric acid were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred at a mass ratio of 0.5:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:4:2.4) to obtain a soy protein adhesive.
[0041] Example 4
[0042] This embodiment provides a method for preparing a highly water-resistant soybean protein adhesive. According to the mass ratio, soybean protein powder: glucose: citric acid = 1:4:2.4. Add a metal catalyst copper chloride (occupying one ten-thousandth of the weight of the adhesive), and the specific steps are as follows:
[0043] 5 parts of glucose, 2 parts of pure water, and 3 parts of citric acid were placed in a 500ml three-necked flask and a metal catalyst copper chloride (occupying one ten-thousandth of the weight of the glue) was added. The three-necked flask was placed in a water bath at 80°C and kept submerged above the sample height. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred at a mass ratio of 0.5:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:4:2.4) to obtain a soy protein adhesive.
[0044] Comparative Example 1
[0045] This comparative example provides a method for preparing a soybean protein adhesive. According to the mass ratio, soybean protein powder: glucose: citric acid = 1:1.6:0. The specific steps are as follows:
[0046] 8 parts of glucose and 2 parts of pure water were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged, and stirred at a constant speed for 3 hours with an electronic stirrer. Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the glucose aqueous solution were mixed and stirred at a mass ratio of 2:1 (i.e., the mass ratio of soy protein powder to glucose was 1:1.6) to obtain an adhesive.
[0047] Comparative Example 2
[0048] This comparative example provides a method for preparing a soybean protein adhesive. According to the mass ratio, soybean protein powder: glucose: citric acid = 1:0:1.6. The specific steps are as follows:
[0049] 2 parts of pure water and 8 parts of citric acid were placed in a 500 ml three-necked flask in a mass ratio, and the three-necked flask was placed in a water bath at 80°C and kept submerged, and stirred at a constant speed for 3 hours with an electronic stirrer. Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the citric acid aqueous solution were mixed and stirred at a mass ratio of 2:1 (i.e., the mass ratio of soy protein powder: citric acid was 1:1.6) to obtain an adhesive.
[0050] Comparative Example 3
[0051] This comparative example provides a method for preparing a soybean protein adhesive. According to the mass ratio, soybean protein powder: glucose: citric acid = 1:3.2:2.4. The specific steps are as follows:
[0052] 4 parts of glucose, 3 parts of pure water and 3 parts of citric acid were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred at a mass ratio of 0.5:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:3.2:2.4) to obtain an adhesive.
[0053] Comparative Example 4
[0054] This comparative example provides a method for preparing a soybean protein adhesive. According to the mass ratio, soybean protein powder: glucose: citric acid = 1:4.8:2.4. The specific steps are as follows:
[0055] 6 parts of glucose, 1 part of pure water and 3 parts of citric acid were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred at a mass ratio of 0.5:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:4.8:2.4) to obtain an adhesive.
[0056] Comparative Example 5
[0057] This comparative example provides a method for preparing a soybean protein adhesive. According to the mass ratio, soybean protein powder: glucose: citric acid = 1:4:1.6. The specific steps are as follows:
[0058] 5 parts of glucose, 3 parts of pure water, and 2 parts of citric acid were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform. The mass fraction of soy protein was 25%. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred at a mass ratio of 0.5:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:4:1.6) to obtain an adhesive.
[0059] Comparative Example 6
[0060] This comparative example provides a method for preparing a soybean protein adhesive. According to the mass ratio, soybean protein powder: glucose: citric acid = 1:4:3.2. The specific steps are as follows:
[0061] 5 parts of glucose, 1 part of pure water, and 4 parts of citric acid were placed in a 500ml three-necked flask, and the three-necked flask was placed in a water bath at 80°C and kept submerged. The mixture was stirred at a constant speed for 3 hours with an electronic stirrer to obtain a yellow-brown transparent mixed crosslinking agent (GA). Soy protein powder was added to pure water and stirred for 5 minutes until it was uniform, so that the mass fraction of soy protein was 25%. The soy protein solution (P) and the mixed crosslinking agent of glucose and citric acid (GA) were mixed and stirred at a mass ratio of 0.5:1 (i.e., the mass ratio of soy protein powder: glucose: citric acid was 1:4:3.2) to obtain an adhesive.
[0062] The prepared soy protein solution was used to bond the double-layer poplar veneer and the prepared adhesive was used to bond the three-layer poplar plywood. The poplar veneer had a specification of 160 mm × 190 mm × 2 mm. The glue application amount on both sides of the middle layer veneer was 200 g / m 2 The glue application area is 25mm×25mm, the hot pressing temperatures are 140℃, 150℃, 170℃, 180℃, and 190℃, the pressing time is 5min, and the pressure is 1.2MPa. The performance test is carried out, and the test results are shown in Table 1.
[0063] Table 1: Statistical table of bonding strength of plywood
[0064]
[0065] The environmentally friendly green soybean protein-based wood adhesive of the present invention replaces traditional adhesives and is of great significance to sustainable development strategies and human health. Soy protein has many active functional groups in its structure. Simply using a cross-linking agent to cross-link it can greatly improve its mechanical properties and water resistance. Glucose and citric acid are pre-heat-treated to prepare a green cross-linking agent (GA), which is added to the soybean protein solution and hot-pressed to undergo esterification and amidation reactions to form a cross-linked network structure. A strong ester absorption peak (1734cm -1); at the same time, XRD analysis shows that the degree of crystallinity after curing is significantly higher than that of soybean protein. This is because a chemical reaction occurs in the cured PGA, causing the molecular chains to cross-link and fold, verifying the high water resistance. Under the condition that the requirements of the national secondary board standard (GB / T17657-2013) (≥0.70MPa) are met, the hot pressing temperature is 170℃, and the wet tensile strength after immersion in hot water at 63℃ for 3h reaches 1.11MPa, and the wet tensile strength after immersion in boiling water at 170℃ reaches 1.07MPa; when the pressing plate temperature is 180℃, the bonding performance after immersion in hot water at 63℃ for 3h reaches 1.62MPa, and the bonding performance after immersion in boiling water for 3h still reaches 1.48MPa; and when the pressing plate temperature is 190℃, the bonding performance after immersion in hot water at 63℃ for 3h reaches 1.72MPa, and the bonding performance after immersion in boiling water for 3h still reaches 1.57MPa, which are all higher than the requirements of the shear strength test of the Chinese national standard (GB / T 17657-2013) (≥0.70MPa). After the three-layer board hot pressed for 5min at 190℃ and immersed in boiling water for 3h, the wood breakage rate is close to 90%. By adding metal catalysts such as copper chloride, the prepared adhesive meets the requirements of Class II boards (shear strength greater than 0.7MPa in 63°C hot water for 3 hours) and the hot pressing temperature is lower, but the mechanical properties at high temperatures are higher than those at low temperatures. This formaldehyde-free, high-water-resistant soy protein adhesive with a relatively low curing temperature has shown broad application prospects in the artificial board industry.
[0066] This patent is funded by Yunnan Province Major Science and Technology Project (202402AE090027).
[0067] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly water-resistant soybean protein adhesive, characterized in that: The soy protein adhesive is resistant to boiling water for at least 3 hours. The preparation method of the soy protein adhesive comprises the following steps: S1, preparing a cross-linking agent by pre-heat treatment of glucose and citric acid; S2, adding the cross-linking agent into the soybean protein solution, and mixing to obtain a process solution; S3, hot-pressing the process solution to make it undergo esterification and amidation reactions to obtain the highly water-resistant soybean protein adhesive.
2. The preparation method according to claim 1, characterized in that Step S2 further includes adding a metal catalyst into the process solution, wherein the metal catalyst includes any one of copper chloride, copper oxide or Collins reagent.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of soybean protein, glucose and citric acid in the process solution is 1:(1-4):(0.6-2.4).
4. The preparation method according to claim 1 or 2, characterized in that: The temperature of the heat treatment in step S1 is 70-80°C.
5. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the cross-linking agent to the soybean protein solution is 1:(0.5-2).
6. A formaldehyde-free adhesive, characterized in that: The method comprises the soybean protein adhesive as described in any one of claims 1 to 5.
7. Use of the soy protein adhesive according to any one of claims 1 to 5 or the adhesive according to claim 6 in the preparation of artificial board products.
8. The use according to claim 7, characterized in that The man-made board product includes any one of plywood, particle board, fiberboard, blockboard and decorative board.
9. A method for preparing plywood, characterized in that: The soy protein adhesive as claimed in claim 5 was used for bonding, at 200g / m 2 The board is glued on both sides with a certain amount of glue and then hot pressed. The hot pressing temperature is 170-190℃, the pressure is 1.2MPa, the hot pressing time is 5min, and the hot pressing process adopts dry heat method.
10. A plywood, characterized in that: The method according to claim 9 is used to prepare the product.